Multi-coupled single scattering method of solving vector radiative transfer equations - 孙斌 王涵 孙晓兵 洪津 张运杰 (Chinese physics B, 2012)
A new method of multi-coupled single scattering （MCSS） for solving a vector radiative transfer equation is de- veloped and made public on Internet. Recent solutions from Chandrasekhar＇s X-Y method is used to validate the MCSS＇s result, which shows high precision. The MCSS method is theoretically simple and clear, so it can be easily and credibly extended to the simulation of aerosol/cloud atmosphere＇s radiative properties, which provides effective support for research into polarized remote sensing.